2008
DOI: 10.35196/rfm.2008.especial_3.9
|View full text |Cite
|
Sign up to set email alerts
|

Calidad De Grano, Tortillas Y Botanas De Dos Variedades De Maíz De La Raza Comiteco

Abstract: Se utilizaron granos de las variedades ‘V-229’ y ‘V-231A’ de maíz (Zea mays L.) para determinar sus propiedades físicas y químicas y su calidad para tortillas y botanas. La variedad ‘V-229’ produjo grano mediano de color crema, con textura intermedia y alto porcentaje de proteína (11.2 %), con 3.9, 0.29 y 0.07 % de aceite, lisina y triptofano, respectivamente; la humedad de su nixtamal fue de 39.6 % y la de sus tortillas de 41 %, con pérdida de sólidos de 3.2 % y una retención de pericarpio de 42.5 %, lo que s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
1
3
1
Order By: Relevance
“…Pericarp values are within acceptable ranges for the nixtamalized flour industry (4.5 to 5.5 mg) and are higher than those obtained for the Pollito variety and lower for H-WP8063. The retained pericarp values published by Coutiño-Estrada et al (2008) are also similar with improved varieties in Chiapas. The flour industry requires values higher than 40 % in this indicator.…”
Section: Figure 1 Grouping Dendrogram Of Local Maize Varietiessupporting
confidence: 67%
See 4 more Smart Citations
“…Pericarp values are within acceptable ranges for the nixtamalized flour industry (4.5 to 5.5 mg) and are higher than those obtained for the Pollito variety and lower for H-WP8063. The retained pericarp values published by Coutiño-Estrada et al (2008) are also similar with improved varieties in Chiapas. The flour industry requires values higher than 40 % in this indicator.…”
Section: Figure 1 Grouping Dendrogram Of Local Maize Varietiessupporting
confidence: 67%
“…For "tortilla" quality, it is important that maize have the capacity to absorb water and retain it, which is reflected in "tortilla" yield (Vázquez-Carrillo et al, 2014). The "tortilla" yield values obtained in this research are higher than those reported by Sierra-Macías et al (2016) andCoutiño-Estrada et al (2008). This capacity is indirectly related to grain hardness and starch composition; the modification of the amylose/amylopectin ratio in the flours influenced the hardness and color of the "tortillas", as well as, the moisture conservation (Salinas-Moreno et al, 2010).…”
Section: Figure 1 Grouping Dendrogram Of Local Maize Varietiescontrasting
confidence: 51%
See 3 more Smart Citations